The rationality and reliability of expectations reported by British households: micro evidence from the British household panel survey - James Mitchell; Martin R. Weale (Deutsche Bundesbank, 2007)
This paper assesses the accuracy of individuals' expectations of their financial circumstances, as reported in the British Household Panel Survey, as predictors of outcomes and identifies what factors influence their reliability. As the data are qualitative bivariate ordered probit models, appropriately identified, are estimated to draw out the differential effect of information on expectations and realisations. Rationality is then tested and we seek to explain deviations of realisations from expectations at a micro-economic level, possibly with reference to macroeconomic shocks. A bivariate regime-switching ordered probit model, distinguishing between states of rationality and irrationality, is then estimated to identify whether individual characteristics affect the probability of an individual using some alternative model to rationality to form their expectations.
Keywords: D84; D19; 330; household behaviour; expectation formation; Rationale Erwartung; Einkommen; Schock; Probit-Modell; Großbritannien